Pourquoi la Catalogne ne peut-elle pas s’autodéterminer ? Les raisons de l'État espagnol - Lucía Payero López (Cahiers de Civilisation Espagnole Contemporaine)
This article analyzes the discourse used by the so-called ‘No’ Bloc –comprised of the two majority parties in the Congress of Deputies (the People’s Party and the Spanish Socialist Workers’ Party), as well as Citizens Party and Union Progress and Democracy– in order to respond to the challenge posed by Catalan pro-sovereign parties. These political groups conceive of Spain as a unitary nation and their rhetoric against self-determination is focused on two main arguments: law and certain supra-positivist limits. The key elements of this reasoning and how legal and extra-legal assumptions are interwoven will be examined. Similarities between the ‘No’ political discourse and the case law of the Constitutional Court will also be highlighted.